TRUTH – GROUND FOR TARAS SHEVCHENKO’S CREATIVE WORK - Makarovsky, I. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the concept of "truth" as the basis of creativity and activity Shevchenko, specifies its main features.